Selective sensing of citrate by a supramolecular 1,8-naphthalimide/calix[4] arene assembly via complexation-modulated pKa shifts in a ternary complex - Schatz, Jürgen; et al. (Journal of Organic Chemistry, 2007)
(Figure Presented) A water-soluble supramolecular sensing assembly, composed of an imidazolium-substituted calix[4]arene and a fluorescent aminodiacetate derivative of 1,8-naphthalimide, was studied. Addition of citrate led to a large fluorescence enhancement, while tartrate, acetate, as well as selected inorganic anions gave smaller effects. The sensing principle and selectivity for citrate rely on the formation of a ternary fluorophore-host- anion complex and complexation-induced pK shifts of an amino group attached to the fluorophore. The complexation of citrate induces a protonation of the amino group, which switches off intramolecular photoinduced electron transfer as the fluorescence quenching pathway, leading to an enhancement of the optical output signal. The intricate sensor principle was corroborated by pH titrations, binding constants, and structural information as obtained by H NMR spectroscopy. © 2007 American Chemical Society.